2016
DOI: 10.1002/2015jd023876
|View full text |Cite
|
Sign up to set email alerts
|

Bias characterization of CrIS shortwave temperature sounding channels using fast NLTE model and GFS forecast field

Abstract: The strong nonlocal thermal equilibrium (NLTE) emission in the upper atmosphere impedes the usage of Cross-track Infrared Sounder (CrIS) temperature channels near 4.3 μm in the operational data assimilation. This study explores the bias characteristics of those temperature channels near 4.3 μm with and without a fast NLTE model implemented in the Community Radiative Transfer Model (CRTM). It is shown that the biases of those temperature channels can reach up to 12 K and are dramatically reduced to below 4 K du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…To investigate this finding theoretically, we performed non-LTE CRTM calculations (e.g., Chen et al 2013;Yin 2016) to derive temperature kernel functions for all AIRS 15 and 4.3 mm channels at a range of different solar zenith angles x. Background temperature and constituent profiles were kept fixed in all cases.…”
Section: Postmission Assessments and Validationmentioning
confidence: 99%
“…To investigate this finding theoretically, we performed non-LTE CRTM calculations (e.g., Chen et al 2013;Yin 2016) to derive temperature kernel functions for all AIRS 15 and 4.3 mm channels at a range of different solar zenith angles x. Background temperature and constituent profiles were kept fixed in all cases.…”
Section: Postmission Assessments and Validationmentioning
confidence: 99%
“…AIRS, IASI and CrIS). The departures of satellite observations from model simulations of these sounders that are on board polar‐orbit satellites often vary with the scan angle and geographic latitude (McNally et al ., ; Yin, ; Li and Zou, ). So, the widely adopted approaches for bias correction are scan angle BC and air‐mass BC (Susskind et al ., ; Eyre, ; Harris and Kelly, ; Auligne et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…() argued that the most appropriate way to study the bias characteristics of O – B for NWP systems is to use the short‐term forecast field as the background field. Also, considering that the forecast field is the next background field in the operational data assimilation system cycle (Yin, ), the GRAPES (Global/Regional Assimilation and Prediction Enhanced System)‐GFS (Global Forecast System) 6 hr forecast field is used as input to the radiative transfer model (RTTOV) for this study instead of the reanalysis fields. This will be conducive to the realization of GIIRS assimilation in the operational data assimilation system.…”
Section: Introductionmentioning
confidence: 99%
“…All fast NLTE simulation studies found large discrepancies between B and O for large SZA in the high‐latitude region of the winter hemisphere. DeSouza‐Machado et al (2007) and Yin (2016) attributed this large discrepancy to the decreased accuracy of NWP profiles in the upper atmosphere for high latitudes. While the discrepancy is slightly reduced, it remains quite large after replacing GFS with the European Centre for Medium‐Range Weather Forecasts (ECMWF) Re‐Analysis (ERA) interim data (Yin, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Their evaluation shows a small bias (~ −0.5 K) and standard deviation of differences (STD) (less than 1.0 K) of background minus observation (BMO) for nadir observations with SZA less than 70° globally. Yin (2016) compared calculated nominal spectral resolution (NSR) CrIS/S‐NPP radiances with the CRTM using the Global Forecast System (GFS) forecast against CrIS observations over North and South Americas including the adjacent oceans. He showed that the BMO bias and STD from daytime after NLTE correction using the CRTM are comparable to those from nighttime without NLTE correction.…”
Section: Introductionmentioning
confidence: 99%